2011
DOI: 10.4028/www.scientific.net/amr.396-398.1615
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Germination on the Bio-Functional Components in the Germ-Remaining Polished Rice

Abstract: The effects of germination on the bio-functional components in the germ-remaining polished rice have been investigated. The bio-functional components in the raw GRPR, brown rice and germinated brown rice were also characterized as the comparison. The results showed that a decrease in amylose content and an increase in reducing sugar were observed after germination. The germinated GRPR contains much more bio-functional components (GABA and dietary fiber) than GRPR and brown rice, and slightly less than germinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Jiamyangyuen and Ooraikul [59] had reported also that GBR had lower amylose content consistent with reports in which activation of amylase enzyme was responsible for higher amounts of bioactives in GBR [60]. Musa et al [36], Li et al [41], and Liu et al [42] also showed that amylose was significantly decreased in BR when subjected to germination. GABA is the most extensively studied GBR bioactive compound, and several studies have shown that it is increased during germination of BR [21, 22, 25, 27–30, 32, 33, 37, 39–41, 43, 59].…”
Section: Germination Of Brown Ricesupporting
confidence: 74%
See 1 more Smart Citation
“…Jiamyangyuen and Ooraikul [59] had reported also that GBR had lower amylose content consistent with reports in which activation of amylase enzyme was responsible for higher amounts of bioactives in GBR [60]. Musa et al [36], Li et al [41], and Liu et al [42] also showed that amylose was significantly decreased in BR when subjected to germination. GABA is the most extensively studied GBR bioactive compound, and several studies have shown that it is increased during germination of BR [21, 22, 25, 27–30, 32, 33, 37, 39–41, 43, 59].…”
Section: Germination Of Brown Ricesupporting
confidence: 74%
“…Musa et al [36], Li et al [41], and Liu et al [42] also showed that amylose was significantly decreased in BR when subjected to germination. GABA is the most extensively studied GBR bioactive compound, and several studies have shown that it is increased during germination of BR [21, 22, 25, 27–30, 32, 33, 37, 39–41, 43, 59]. Similarly, Jayadeep and Malleshi [34] reported increased free sugars, insoluble fibre, and other bioactives following biotransformation of BR.…”
Section: Germination Of Brown Ricementioning
confidence: 99%